Working-Class Standards of Living in Late-Victorian Urban Ontario: A Review of the Miscellaneous Evidence on the Quality of Material Life - Gagan, David; Gagan, Rosemary (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1990)
AbstractOwing to the lack of long series of data pertaining to wages and retail prices, the analysis of standards of living in late-Victorian Ontario presents unusually difficult problems for the social historian. Following the model adopted by the participants in the earlier British standard-of-living debate, this study attempts to mitigate those difficulties, to some extent, by examining a wide range of miscellaneous sociological and economic evidence generated by government agencies, usually for other purposes. A review of the data pertaining to employment, wages, savings, consumption, the accumulation of real wealth, public health and social pathology in urban Ontario between 1875 and 1900 suggests that the 1880s was a decade of rising expectations in terms of employment, consumption, savings and the distribution of wealth following the social and economic upheaval associated with the depression of the late 1870s. However, the evidence also suggests that the marginal gains made in working-class standards of living in the 1880s were largely compromised in the 1890s as the environmental effects of industrialization and urbanization began to be experienced in full measure.